CCDC110 promotes the progression of hepatocellular carcinoma by activating the TGF-β/SMAD signaling pathway through targeted regulation of TGFBR1 - Hao Shen; Haifeng Li; Haodong Tang (Cancer Cell International)
Abstract Background Hepatocellular carcinoma (HCC) is recognized for its high growth rate, high degree of invasiveness, and tendency to spread, leading to a significant number of deaths. In the course of studying the transcriptome of HCC tissues, the protein coiled-coil domain-containing 110 (CCDC110) was identified. By employing tandem mass tag (TMT) quantitative proteomics, this research identified transforming growth factor beta receptor 1 (TGFBR1) as a potential target influenced by CCDC110. The purpose of this study was to examine the role of CCDC110 in the growth and invasion of HCC and to identify new potential targets for the treatment of HCC. Methods In vitro and in vivo experiments were conducted to investigate the role and mechanism of CCDC110 in promoting the malignant behaviors of hepatocellular carcinoma through the regulation of TGFBR1. Results We determined that the mRNA and protein levels of CCDC110 are elevated in hepatocellular carcinoma tissues and cell lines, which is correlated with a worse patient prognosis. CCDC110 enhances the proliferation of hepatocellular carcinoma cells, reduces their apoptosis, and increases their migration and invasion capabilities. In the cytoplasm, CCDC110 interacts with TGFBR1, enhancing stability of TGFBR1, promoting proliferation, and reducing the apoptosis, migration, and invasion of hepatocellular carcinoma cells through TGFBR1 both in vivo and in vitro. The CCDC110-TGFBR1 axis stimulates EMT, thereby enhancing the malignant biological behavior of hepatocellular carcinoma by activating the TGF-β/SMAD signaling pathway. The protein levels of CCDC110/TGFBR1 in hepatocellular carcinoma tissues are highly expressed and positively correlated. A combined analysis of CCDC110 and TGFBR1 provides improved guidance for the prognosis of patients with hepatocellular carcinoma. Conclusion CCDC110 is highly expressed in hepatocellular carcinoma tissues and cell lines, and the CCDC110-TGFBR1 axis facilitates EMT and the malignant biological behavior of hepatocellular carcinoma through the activation of the TGF-β/SMAD signaling pathway.